AO-WAD: A Supporting Tool to Aspect-Oriented Web Accessibility Design - Mazalu, Rafaela (2011)
There are a number of tools and proposals to help developers assess Accessibility of Web applications; however looking from the designer perspective, there is no such a similar situation. In this paper, we present a supporting tool that helps users model Web Accessibility by moving from abstract to concrete architectural views using aspect-orientation. Thus, the designers and developers produce accessible interfaces. The proposed tool is based on an approach that takes advantages of modeling Accessibility as an aspect-oriented concern, which is independently treated but related to architectural pieces.